Stealing Time: The Propriety of Alleging Common Law Conversion in Modern Wage Theft Lawsuits - Goldberg, Hilary M.; Carr, Nanci K.; Silvia, Paul J. (Journal of Law and Commerce, 2018)
The words “wage theft” frequently make headlines when workers sue employers for underpayment or nonpayment of wages.[1] Wage theft is “the illegal refusal by an employer to pay a worker the wages and benefits that he or she has legally earned.”[2] In the United States, employer violation of wage and hour laws is a vast and enduring problem, affecting as many as two-thirds of workers. In an attempt to combat this epidemic threat to hourly workers’ bottom lines, legislatures have fashioned numerous laws, some even invoking the power of “wage theft” terminology, such as New York’s Wage Theft Prevention Act.[3] However, despite the pervasive usage of the term “wage theft” by the media, politicians, and pundits, a search of the term “wage theft” in legal libraries yields little precedent. This begs the question: can employers be liable for conversion for failing to compensate employees for time-spent working? The efficacy of conversion claims in wage related lawsuits remains an unsettled question. However, if as a society we are sounding the alarm in every incidence of possible wage and hour law violations, we ultimately misinform the population of potential plaintiffs regarding the viability of a claim for theft, or conversion, of earned yet unpaid wages. The term “wage theft” is not a term of art; its closest legal corollary is the common law tort of conversion. Although we as a society frequently identify underpayment or nonpayment of wages as “wage theft,” pleading and proving that the employer has converted an employee’s wages presents an array of challenges that few plaintiffs can overcome. In this paper, we will explore the term “wage theft” as used in our society, and we will contrast this common understanding with the strict legal framework within which plaintiffs must present “wage theft” claims. Finally, we will explore this disconnect in an attempt to reconcile why such a gap exists, and persists, between the commonplace description of a worker’s reality, and the laws available to make the worker whole again. While it appears the term “wage theft” equates more readily with an exclamation of outrage than an effective claim for relief, its persistence underscores the continuing need for common law remedies, like conversion, to fill in the enforcement gaps left behind by persistently reactive legislation. [1] See Brady Meixell and Ross Eisenbrey, An Epidemic of Wage Theft Is Costing Workers Hundreds of Millions of Dollars a Year, Economic Policy Institute (Sep. 11, 2014), http://www.epi.org/publication/epidemic-wage-theft-costing-workers-hundreds/; Josh Eidelson, LinkedIn Stiffed its Own Employees, Agrees to Pay Millions, BUSINESSWEEK (Aug. 5, 2014), https://www.bloomberg.com/news/articles/2014-08-05/linkedin-stiffed-its-own-employees-agrees-to-pay-millions; and Monica Potts, The Very Real Scourge of Wage Theft, THE DAILY BEAST (Feb. 15, 2015), http://www.thedailybeast.com/articles/2015/02/15/the-very-real-scourge-of-wage-theft.html. [2] Hilda L. Solis, Wage Theft Harms All of Us, The Huffington Post (July 19, 2015), http://www.huffingtonpost.com/hilda-l-solis/wage-theft-harms-all-of-u_b_7829514.html. [3] Wage Theft Prevention Act, 2009 N.Y.S.N. 8380 (Apr. 12, 2011).